Iron deficiency anemia from iron malabsorption caused by proton pump inhibitors. Issue 2 (1st September 2020) - Boxer, Michael
Abstract: Background: Iron deficiency anemia without evidence for blood loss can present a diagnostic challenge. Proton pump inhibitors have been associated with iron deficiency anemia for many years, yet the relationship between the two until recently was not fully understood. Treatment recommendations are lacking. Methods and methods: This study evaluated 43 iron deficient patients who were taking proton pump inhibitors, 41 of whom were unresponsive to oral iron, and for whom no etiology for the iron deficiency could be found. Two patients who had hereditary hemochromatosis never were treated with oral iron. Results: Forty‐three patients taking a proton pump inhibitor had elevated serum gastrin ≥100 pg/mL. Upon treatment with intravenous iron, 95% (41/43) responded with increased hemoglobin concentration ≥2 g/dL. Improvements were also achieved in the mean corpuscular volume, ferritin, and transferrin saturation. Conclusions: These findings suggest that proton pump inhibitors have been an under‐recognized cause for iron deficiency anemia and need to be considered in patients who are taking a proton pump inhibitor. The iron deficiency does correct with intravenous iron replacement.